2018
DOI: 10.1007/s10103-017-2426-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-frequency near-infrared diode laser irradiation on the proliferation and migration of mouse calvarial osteoblasts

Abstract: Laser irradiation activates a range of cellular processes and can promote tissue repair. Here, we examined the effects of high-frequency near-infrared (NIR) diode laser irradiation on the proliferation and migration of mouse calvarial osteoblastic cells (MC3T3-E1). MC3T3-E1 cells were cultured and exposed to high-frequency (30 kHz) 910-nm diode laser irradiation at a dose of 0, 1.42, 2.85, 5.7, or 17.1 J/cm. Cell proliferation was evaluated with BrdU and ATP concentration assays. Cell migration was analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 54 publications
1
20
1
Order By: Relevance
“…In another study, cell proliferation was confirmed by NIR laser irradiation of osteoblast-like cells (MC3T3-E1). 12 However, the cells did not proliferate in the present study. This could be related to the use of a different cell type and differences in experimental methods for confirming cell growth.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…In another study, cell proliferation was confirmed by NIR laser irradiation of osteoblast-like cells (MC3T3-E1). 12 However, the cells did not proliferate in the present study. This could be related to the use of a different cell type and differences in experimental methods for confirming cell growth.…”
Section: Discussioncontrasting
confidence: 68%
“…8,9 Also, another study reports that Nd: YAG laser irradiation promoted osteoblast differentiation, 10 red laser irradiation caused fibroblast proliferation, 11 and diode laser irradiation caused osteoblast proliferation. 12 In the field of orthodontic dentistry, pain relief 13,14 during tooth movement by laser irradiation and the acceleration of tooth movement have been reported. [15][16][17] However, it is currently the case that there are many things the mechanisms of which are not known yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that the signaling pathway for IL-1β-mediated regulation of MMP-13 is different from that for IL-1β-mediated regulation of MMP-1 and MMP-3 and may not involve MEK/ERK activities. Previous studies indicated that high-frequency diode laser irradiation affected ERK activity but not p38 and JNK activity [41,42]. Our qPCR results show that high-frequency diode laser irradiation decreased the IL-1β-induced MMP-1 and MMP-3 expression but did not affect MMP-13 expression.…”
Section: Discussionsupporting
confidence: 49%
“…These devices produce low-level output, high peak power, and no thermal damage to the treated tissue and enable efficient light penetration into the tissue [32,36]. High-frequency near-infrared diode laser irradiation enhanced the proliferation and migration of human gingival epithelial cells [41] and mouse calvarial osteoblasts [42]; promoted epithelialization and bone formation in tooth extraction sockets, possibly by activating cell proliferation and differentiation in vivo [43]; and reduced temporomandibular joint pain [44,45]. Moreover, high-frequency near-infrared diode laser irradiation of periodontal tissue leads to metabolic activation, thereby increasing the tooth movement rate in rats [46].…”
Section: Introductionmentioning
confidence: 99%